A 700-year record of atmospheric circulation developed from the Law Dome ice core, East Antarctica - Souney, JM; Mayewski, PA; Goodwin, ID; Meeker, LD; Morgan, VI; Mark Curran; Tasman van Ommen; Palmer, AS (2002)
A 700-year, high-resolution, multivariate ice core record from Dome Summit South (DSS) (66Â°46'S, 112Â°48'E; 1370 m), Law Dome, is used to investigate sea level pressure (SLP) variability in the region of East Antarctica. Empirical orthogonal function (EOF) analysis reveals that the first EOF (LDEOF1) of the combined glaciochemical, oxygen isotope ratio, and accumulation rate record from DSS represents most of the variability in sea salt seen in the record. LDEOF1 is positively correlated (at least 95% confidence level) to instrumental June mean SLP across most of East Antarctica. Over the last 700 years, LDEOF1 levels at Law Dome were the highest during the nineteenth century, suggesting an increase in intensification of winter circulation during this period. The Law Dome DSS oxygen isotope ratio series also indicates that the nineteenth century had the coldest winters of any century in the record. In contrast, LDEOF1 levels were the lowest at Law Dome during the eighteenth century, suggesting a significant shift in the patterns and/or intensity of East Antarctic atmospheric circulation between the eighteenth and the nineteenth centuries. The LDEOF1 sea salt record is characterized by significant decadal-scale variability with a strong 25-year periodic structure. Copyright 2002 by the American Geophysical Union.